Recruiting Assistance And Collaboration: A West-African Corpus Study - Dingemanse, Mark (My University, 2020)
Doing things for and with others is one of the foundations of human social life. This chapter studies a systematic collection of 207 recruitments of assistance and collaboration from a video corpus of everyday conversations in Siwu, a Kwa language of Ghana. A range of social action formats and semiotic resources reveals how language is adapted to the interactional challenges posed by recruitment. While many of the formats bear a language-specific signature, their sequential and interactional properties show important commonalities across languages. Two tentative findings are put forward for further cross-linguistic examination: a "rule of three" that may play a role in the organization of successive response pursuits, and a striking commonality in animal-oriented recruitments across languages that may be explained by convergent cultural evolution. The Siwu recruitment system emerges as one instance of a sophisticated machinery for organizing collaborative action that transcends language and culture.
Keywords: West African; Collaboration; Siwu